Effect of Chemical Fertilizers on Groundwater Quality in an Unconfined Aquifer - Adesiji, A. R.; Jimoh, O. D.; Adeoye, P. A.; Odofin, A. J.; Asogwa, O. E.; Mangey, J. A.; Odekunle, O. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
The use of fertilizer on soil to improve agricultural yield has been practiced for years. While fertilizers and manures greatly improve crop yield, it is also important to consider their corresponding and devastating effects. In this study, the fertilizers application rate was varied and their effects on groundwater quality with soil depths of 30 cm and 60 cm were observed. Two fabricated lysimeters were used to collect soil samples undisturbed and taken to the laboratory for analyses. The samples in the lysimeters were made saturated and varying quantities of fertilizers from 87.37 g, 100 g. and 120 g were applied. The saturation of the samples was done through an improvised rainfall simulator which was set up in such a way that a constant discharge was adopted. Water samples were collected at 30 cm and 60 cm depths and analyzed for fertilizer residues and physico-chemical characteristics such as temperature, pH, total chloride, total dissolved solids, dissolved oxygen, conductivity, free ammonia, total phosphate, urea, zinc and iron were also analysed. The results showed that the more the quantities of fertilizers applied on the soil, the more it affects the physico-chemical properties of the water and renders it toxic and unsuitable for drinking purposes except treated. The results, however revealed that the concentrations of the fertilizers in the groundwater decreases with soil depths. It is therefore recommended that any groundwater being explored for domestic use close to soil surface in areas prone to fertilizer pollution should be well treated before consumption, most especially for people using shallow wells.